Changes of Microbial Community and Reactor Performance in Sequencing Batch Reactors Under Diclofenac Selective Pressure - Jiang, Cong; Yu, Qingmiao; Li, Shaoli; Hu, Haidong; Ren, Hongqiang; Xu, Ke; Geng, Jinju (Journal of Environmental Science and Engineering Technology, 2020)
The wide use of diclofenac (DCF) ineluctably increases the release into wastewater that might cause potential negative effects on wastewater treatment system. To investigate whether DCF caused adverse impacts on the wastewater treatment efficiency and changes of microbial community structure, the exposure experiments at three levels (0, 5, and 50 µg L-1) were conducted in sequencing batch reactors (SBRs) for 120 days. Results indicated that 50 µg L-1 DCF decreased the chemical oxygen demand (COD) removal by about 10%, but had no obvious effect on the ammonia and total nitrogen removal (p > 0.05). 5 µg L-1 DCF could improve superoxide dismutase (SOD) and succinate dehydrogenase (SDH) activity, while 50 µg L-1 DCF would inhibit SOD and SDH activity. The extracellular polymeric substance (EPS) content increased with the increase of DCF concentration. Compared to the control, Gram-negative bacteria increased and Gram-positive bacteria decreased under 50 µg L-1 DCF pressure. Shannon-Wiener index is calculated by PLFA compositions and 16S rRNA gene pyrosequencing indicating that microbial diversity increased in 5 µg L-1 DCF but decreased in 50 µg L-1 DCF. 16S rRNA gene pyrosequencing results showed that Chloroflexi, OD1, and Firmicutes kept the decreasing tendency with the increase of DCF concentration.